Clinical Adjusted Photodynamic Therapy. Issue 1 (15th April 2013) - Ziolkowska, Maria; Carsten, Carsten M.; Mueller, Ute; Urban, Peter; Berlien, H.‐Peter
Abstract Lasers are currently used in diagnostics, for example in metabolic monitoring (fluorescence diagnosis, laser Doppler) and optical imaging (laser scanning microscopy, optical coherence tomography, infrared diaphanoscopy). One main research focus remains therapeutic applications — on one hand using lasers as a surgical instrument, on the other as a central, independent therapy method. Historically, the traditional indication for photodynamic therapy (PDT) has been malignant tumors, but experience of photodynamic therapy in this field and understanding of the biochemical metabolic processes involved, has expanded the use of this therapeutic principle to benign diseases. But even as developments in surgical applications (for example, the development of "laser scalpels") are recorded in the last few years advancements have also been made in other areas, such as virtual endoscopy in MRI.